2017
DOI: 10.1021/acs.energyfuels.6b03360
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Iron, Copper, Zinc, Aluminum, and Chromium in Biodiesel by Flame Atomic Absorption Spectrometry Using a Microemulsion Preparation Method

Abstract: This work proposes a flame atomic absorption spectrometry (FAAS) method for Fe, Cu, Zn, Al, and Cr determination in biodiesel using water in oil (w/o) microemulsion (ME) as a sample preparation method. A less toxic solvent (n-propanol), instead of those used in the standard method (ABNT NBR 15556), the absence of surfactant, and calibration using inorganic reference standards were investigated. A ternary phase diagram of biodiesel as oil, water, nitric acid, and n-propanol showed a single-phase ME region. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…The stability of S. xiamenensis grafted onto GO/PVA biofilms was evaluated according to the total biomass grafted onto the biofilms measured by the bicinchoninic acid (BCA) method . Additionally, we used a flame atomic absorption spectroscopy (Bio-Rad, US) instrument to measure the concentrations of Cr­(VI) and the diphenylcarbazide spectrophotometric method to measure Cr­(T). , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of S. xiamenensis grafted onto GO/PVA biofilms was evaluated according to the total biomass grafted onto the biofilms measured by the bicinchoninic acid (BCA) method . Additionally, we used a flame atomic absorption spectroscopy (Bio-Rad, US) instrument to measure the concentrations of Cr­(VI) and the diphenylcarbazide spectrophotometric method to measure Cr­(T). , …”
Section: Methodsmentioning
confidence: 99%
“…30 Additionally, we used a flame atomic absorption spectroscopy (Bio-Rad, US) instrument to measure the concentrations of Cr(VI) and the diphenylcarbazide spectrophotometric method to measure Cr(T). 31,32 Data Analysis. Data were analyzed and displayed using the Origin 8.0, Microsoft Excel 2010, and SPSS 20.0 software.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Various analytical methods, like electrochemical methods, inductively coupled plasma atomic emission spectroscopy (ICP-AES) and atomic absorption spectrometry (AAS), have been applied for determining zinc ions [ 13 , 14 ]. However, they require complicated sample preparation, expensive instruments and time-consuming procedures [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain CuNCs with good stability, and a suitability for experimental use, surface ligands can be added for protection during preparation, which can control the stability and rate of nanocrystalline nucleation. In combination with different methods to improve the stability of CuNCs, more synthesis processes and methods have been experimented with, such as water-in-oil (w/o) micro emulsion strategies [ 5 ] and the Brust-Schiffrin method [ 6 ], among others. It is reported that CuNCs have a great potential in optical sensing [ 7 ], environmental monitoring [ 8 ], and medical-related applications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%